Strategi Guru Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pembelajaran Pendidikan Agama Islam Kelas 6 SD Negeri 03 Merigi - Wiwin Nursoleha; Nur Jannah (Yayasan Darusssalam Bengkulu, 2024)
Motivational strategies in learning are a plan that includes a series of activities that are specifically designed and developed to meet certain educational goals. Therefore, it is necessary to realize the goals of an ideal educational plan in accordance with educational values. Therefore, teachers must have a learning motivation strategy to inspire students to learn in a fun, interesting and non-monotonous way. To achieve the goal of increasing student motivation, teachers must increasingly choose and apply motivational strategies, methods, and teaching methods that are in accordance with these abilities. The purpose of this study is to describe the teacher's strategy applied in increasing student learning motivation in Islamic Religious Education subjects and to describe the increase in student learning motivation in Islamic Religious Education subjects. In this study, the researcher applied a qualitative approach, by conducting observations, interviews and documentation at SD Negeri 03 Merigi, to find out the learning methods applied there.